SIRT7-dependent deacetylation of fibrillarin controls histone H2A methylation and rRNA synthesis during the cell cycle - Iyer-Bierhoff, Aishwarya Murali; Ruppert, Thomas; Grummt, Ingrid (Cell reports, 2018)
Fibrillarin (FBL) is a dual-function nucleolar protein that catalyzes 2′-O methylation of pre-rRNA and methylation of histone H2A at glutamine 104 (H2AQ104me). The mechanisms that regulate FBL activity are unexplored. Here, we show that FBL is acetylated at several lysine residues by the acetyltransferase CBP and deacetylated by SIRT7. While reversible acetylation does not impact FBL-mediated pre-rRNA methylation, hyperacetylation impairs the interaction of FBL with histone H2A and chromatin, thereby compromising H2AQ104 methylation (H2AQ104me) and rDNA transcription. SIRT7-dependent deacetylation of FBL ensures H2AQ104me and high levels of rRNA synthesis during interphase. At the onset of mitosis, nucleolar disassembly is accompanied by hyperacetylation of FBL, loss of H2AQ104me, and repression of polymerase I (Pol I) transcription. Overexpression of an acetylation-deficient, but not an acetylation-mimicking, FBL mutant restores H2AQ104me and transcriptional activity. The results reveal that SIRT7-dependent deacetylation impacts nucleolar activity by an FBL-driven circuitry that mediates cell-cycle-dependent fluctuation of rDNA transcription.
Gesehen am 20.02.2020